Impact of Logic in Architectural Design Process on Architecture Identity - Abdullah Yousif , Hawar; Yousif Tayib , Abdullah (The Scientific Journal of Cihan University– Sulaimaniya, 2025)
The research deals with the concept of logic as a design approach that affects the architecture identity. The research question is: “Does logic in architectural design process affect the architecture identity?”. By reviewing many studies that have dealt with the concept of logic in the architectural design process, it became clear that they did not shed light on this complex relationship between it and the architecture identity. Hence, the research problem arose and the gap emerged, which is the lack of scientific knowledge of the relationship between logic as a design method and the concept of architectural identity. The research aims to answer the question by clarifying this relationship to know the extent of the relationship between the variables by building a theoretical framework that explains the logic in the architectural design process and the architecture identity, in addition to conducting a practical study that includes a graphic analysis of architectural models in the city of Dohuk - Iraqi Kurdistan. The research methodology included the following: determining the architectural design variables extracted from the theoretical framework (basic geometric shapes, monomorphic or unified shape, ornaments and manufactured details, smooth finishes, pattern repetition, orthogonal grid, golden ratio, new manufactured materials, compatible binary colors, and continuous or strip windows) in addition to determining the research sample, measurement method, statistical and graphic analysis of variables. The results showed that there is a tendency towards logical and rational architecture by focusing on the use of the aforementioned vocabulary in the stages of the design process. These variables also varied in the intensity of their impact on the identity of architecture, and this indicates the difference in the intensity of their effectiveness in achieving this. The conclusion shows how the use of these variables and the focus on them in the logical stages of the architectural design process (analysis, synthesis, and evaluation) negatively affects the failure to highlight the identity and character of architecture through the production of buildings devoid of architectural meanings and connotations lacking local and cultural identity and regional distinction.